Through the Word: Works by Carmela Gross and Rubens Gerchman - Mafra, Juliana; Alcântara, Thiago (Farol, 2026)
This research analyzes works by Carmela Gross and Rubens Gerchman—pieces that either feature the written word on their surfaces or embody the structure itself—aiming to understand the specific use of this imagistic and narrative device through a literature-based critique. The study identifies that the urban context and violence drive these artistic endeavors, leading to the conclusion that, for these artists, art constitutes a political territory as well as a space for reflecting on the conceptual nature of the written word.
Keywords: criticism; language; politics; Carmela Gross; Rubens Gerchman